Molecular typing of the yeast species Dekkera bruxellensis and Pichia guilliermondii recovered from wine related sources - Malfeito-Ferreira, Manuel (2009)
A total of 63 strains of Dekkera bruxellensis and 32 strains of Pichia guilliermondii isolated from wine related environments were identified by restriction analysis of the 5.8S-ITS region of the rDNA. These strains were subjected to intraspecific discrimination using mtDNA restriction and RAPD-PCR analysis. The isolates identified as D. bruxellensis yielded 3 different molecular patterns of mtDNA restriction using the endonuclease HinfI. The pattern A was the most frequent (58 strains) among strains from different sources, regions and countries. Pattern B (4 strains) and C (one strain) were determined in isolates from Portuguese wines. The discrimination among the pattern A strains was achieved by a RAPD-PCR assay with 3 primers (OPA-2, OPA-3 and OPA-9). A total of 12 haplotypes were obtained with the combination of the patterns provided by the 3 OPAs. The pattern 2 was the most frequent and extensively distributed being found in strains from different countries and from different sources like wine, barrique wood and insects. The strains of P. guilliermondii were characterized with restriction of mtDNA using the endonuclease HinfI yielding 7 different restriction patterns. These patterns were associated with different efficiencies of 4-ethylphenol production. Patterns A to D corresponded to 19 strains producing low levels of 4-ethylphenol (<1 mg/l) while patterns F and G grouped 13 strains producing high levels of 4-ethylphenol (>50 mg/l), when grown in synthetic media supplemented with 100 mg/l of p-coumaric acid. The high degree of polymorphism observed shows that intraspecific typing is essential for accurate yeast dissemination studies in wine related environments.